Basic Life Support Workshop 2025 Heart: Hear, Evaluate, Act, Resuscitate and Train - Nolly O. H. Rantung (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Background:The Community Service Activity entitled “2025 Basic Life Support Workshop: HEART (Hear, Evaluate, Action, Resuscitate, Training)” was implemented as an effort to improve preparedness and basic skills in handling emergencies in the community, especially among high school students. Objective: This activity aims to provide fast and appropriate initial treatment to increase the victim's chances of survival and minimize the risk of complications. Method: This activity was held at SMAN 67 Jakarta on April 26, 2025 and was attended by 40 students as active participants. The implementation method included a series of educational and interactive activities, consisting of material counseling on the concept and stages of Basic Life Support (BLS), basic skills training in dealing with cardiac arrest and respiratory distress situations, as well as direct practice and educational games to strengthen participants' understanding. Through the HEART (Hear, Evaluate, Action, Resuscitate, Training) approach, participants were trained to recognize emergency signs, evaluate the victim's condition quickly, take appropriate action, and perform cardiopulmonary resuscitation (CPR) according to standards. Results: The results of the activity showed an average increase in participants' knowledge scores of 42.5% after the training, with 90% of participants able to demonstrate CPR steps with the correct sequence and technique. In addition, 85% of participants stated that they were more confident in providing first aid in emergencies. The activity also received a positive response, with a 95% level of participant satisfaction with the relevance and learning methods used. Conclusion: It can be concluded that the 2025 Basic Life Support Workshop: HEART Training successfully increased students' knowledge, skills, and confidence in dealing with medical emergencies. This program is expected to become a model for sustainable education in the school environment to build a young generation that is responsive, caring, and skilled in helping others.